2013
DOI: 10.1159/000354757
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Resistance in Breast Cancer: Focus on the Phosphatidylinositol 3-Kinase/Akt/Mammalian Target of Rapamycin Signaling Pathway

Abstract: Breast cancer is the most common cancer among women. Up to 75% of breast cancers express the estrogen receptor (ER)α and/or the progesterone receptor (PR). Patients with hormone receptor-positive metastatic breast cancer are typically treated with endocrine therapy. Yet, not all patients with metastatic breast cancer respond to endocrine treatments and are considered to have primary (de novo) resistance. Furthermore, all patients who initially respond to endocrine treatment will eventually develop acquired res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…1) [9]. The respective receptor dimerizes, is autophosphorylated and recruits adaptor proteins such as insulin receptor substrate (IRS)1 and IRS2.…”
Section: The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…1) [9]. The respective receptor dimerizes, is autophosphorylated and recruits adaptor proteins such as insulin receptor substrate (IRS)1 and IRS2.…”
Section: The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%
“…Activation of mTORC1 also leads to a negative feedback loop [9]. Direct inhibition of mTORC1 by an administered treatment can suspend the negative feedback loop, leading to the paradoxical activation of the signaling pathway and expression of multiple receptor tyrosine kinases such as HER2 and the IGF-1 receptor (IGF-1R) [11].…”
Section: The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic and cell survival signals are also dysregulated in TAM-resistant cells (Riggins et al 2005). A more extensive review of mechanisms promoting endocrine resistance can be found in (Hasson, et al 2013; Musgrove and Sutherland 2009; Zhao and Ramaswamy 2014). Additional factors are continually identified as playing roles in endocrine resistance.…”
Section: Overview Of Mechanisms Of Endocrine Resistancementioning
confidence: 99%
“…As reported in the third review article of this journal's edition by Hasson and colleagues [6], even if the mechanism of crosstalk between the mTOR and HR pathways are not well described, clinical data support the use of mTOR inhibitors in patients who developed resistance to endocrine treatment. In metastatic breast cancer, the addition of an mTOR inhibitor has shown a gain in survival when combined either with an aromatase inhibitor or with tamoxifen.…”
mentioning
confidence: 99%